Time protective effect of contact with a general practitioner and its association with diabetes-related hospitalisations: a cohort study using the 45 and Up Study data in Australia - Rachael Moorin; Mark Harris; David Preen; Ninh Thi Ha (BMJ Open)
Objectives To evaluate the relationship between the proportion of time under the potentially protective effect of a general practitioner (GP) captured using the Cover Index and diabetes-related hospitalisation and length of stay (LOS).Design An observational cohort study over two 3-year time periods (2009/2010–2011/2012 as the baseline and 2012/2013–2014/2015 as the follow-up).Setting Linked self-report and administrative health service data at individual level from the 45 and Up Study in New South Wales, Australia.Participants A total of 21 965 individuals aged 45 years and older identified with diabetes before July 2009 were included in this study.Main outcome measures Diabetes-related hospitalisation, unplanned diabetes-related hospitalisation and LOS of diabetes-related hospitalisation and unplanned diabetes-related hospitalisation.Methods The average annual GP cover index over a 3-year period was calculated using information obtained from Australian Medicare and hospitalisation. The effect of exposure to different levels of the cover on the main outcomes was estimated using negative binomial models weighted for inverse probability of treatment weight to control for observed covariate imbalance at the baseline period.Results Perfect GP cover was observed among 53% of people with diabetes in the study cohort. Compared with perfect level of GP cover, having lower levels of GP cover including high (incidence rate ratio (IRR) 2.8, 95% CI 2.6 to 3.0), medium (IRR 3.2, 95% CI 2.7 to 3.8) and low (IRR 3.1, 95% CI 2.0 to 4.9) were significantly associated with higher number of diabetes-related hospitalisation. Similar association was observed between the different levels of GP cover and other outcomes including LOS for diabetes-related hospitalisation, unplanned diabetes-related hospitalisation and LOS for unplanned diabetes-related hospitalisation.Conclusions Measuring longitudinal continuity in terms of time under cover of GP care may offer opportunities to optimise the performance of primary healthcare and reduce secondary care costs in the management of diabetes.